The role of Metacognition on effect of Working Memory Capacity on students' mathematical problem solving (European Journal of Child Development, Education and Psychopathology, 2013)
The main objective of this study was to investigate the effects of Working Memory Capacity (WMC) on students' mathematical problem solving while considering different psychological factors. A sample of 256 high school girls students from Tehran (17-18 years old) were tested on (a) Metacognitive Awareness Inventory (MAI), (b) Mathematics Attention Test (MAT), (c) Mathematics Anxiety Rating Scale (MARS), (d) Digit Span Backward Test (DBT), and (e) a Mathematics Exam. Data of the present study were analyzed by descriptive and inferential statistics by T-test and Spearman correlation with the Statistical Package for the Social Sciences (SPSS). Results obtained indicate that metacognition had distinctive and challenging variable than other factors in use of WMC in mathematical problem solving. In other words, the correlation superiority between WMC and mathematical performance was found in group of high metacognition. Moreover, in each group of low/high metacognition, low/high math attention, and low/high math anxiety, the students with high WMC showed better mathematical performance than low WMC ones. The findings of the study are suitable for researchers who interested how different factors influence students’ mathematical problems solving.